(3GdbUjOI GdcejJjI HJaSjQgG heYGfjgGs ((3Ydi Hf RjO Hf CMeO Hf jMji s)
(3ChdgG (B:s
(3eHJhQ , hjHOC GdehLhO efgG Hbhdg (B: (3Gde JJYLHi ef QjH GdOgQ QCjJ XghQg bdHJ HWhfkG s
(3BNQgG (B:s
(3cHjJ GdYfcHhJ hLOJ HjJkG jeO bVGYg (B( (3?(B) (3CLeYfG fSH bVGYI Edi bdI GdYOO , ceG bGd GdWQeGM Hf Mcje GdWGFQi (B: (3hdh Cf Ce GdYfcHhJ HfJ dge eXJgG jhe GddbGA CXdJ JeJ GdbUjOI GdcejJjI HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdCOHs